Late Pleistocene Age of the Type Temple Lake Moraine, Wind River Range, Wyoming, U.S.A. - Zielinski, Gregory; Thompson Davis, P. (Géographie physique et Quaternaire, 1987)
ABSTRACTThe type Temple Lake moraine lies about 3 km beyond and roughly 120 m lower than the modern glacier margin and the Gannett Peak (Little Ice Age) moraines deposited in the last few centuries. Because numerous glacial deposits throughout the western United States have been correlated to the Temple Lake moraine its age is important. We retrieved two sediment cores up to six meters long from Rapid Lake, outside the outer type Temple Lake moraine. The 383-413 cm depth dates 11,770 ± 710 yrs (GX-11,772), which we believe reflects the time when silt flux into Rapid Lake was abruptly reduced by the formation of a new sediment trap at Miller Lake as the valley glacier receded from its position at the outer Temple Lake moraine. A radiocarbon date of 11,400 ± 630 yrs BP (GX-12,719) obtained from the lower basin of Temple Lake, inside the inner type Temple Lake moraine, supports this interpretation. Sediments from Miller Lake, inside the outer Temple Lake moraine, that date 8300 ± 475 yrs BP (GX-12,277) are probably well above the bottom of the lake sediment sequence and possibly thousands of years younger than the moraine. We feel that the type Temple Lake moraine dates about 12,000 yrs BP, thus is Late Pleistocene in age. This interpretation is supported by maximum percentages of organic detritus in lake sediments between 10,000 and 8,000 yrs BP, and challenges BEGET's (1983) suggestion that the type Temple Lake moraine is early Holocene in age, a period he calls "Mesogiaciation".